2008
DOI: 10.1007/s00239-008-9180-7
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reorganization of the Plastid Genome of Trifolium subterraneum (Fabaceae) Is Associated with Numerous Repeated Sequences and Novel DNA Insertions

Abstract: The plastid genome of Trifolium subterraneum is 144,763 bp, about 20 kb longer than those of closely related legumes, which also lost one copy of the large inverted repeat (IR). The genome has undergone extensive genomic reconfiguration, including the loss of six genes (accD, infA, rpl22, rps16, rps18, and ycf1) and two introns (clpP and rps12) and numerous gene order changes, attributable to 14-18 inversions. All endpoints of rearranged gene clusters are flanked by repeated sequences, tRNAs, or pseudogenes. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
243
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(264 citation statements)
references
References 46 publications
12
243
2
1
Order By: Relevance
“…Plastome organization, gene content, and gene order are generally well conserved among flowering plants. However, recent complete sequencing revealed that the plastomes in a few plant families, such as the Campanulaceae, Fabaceae, and Geraniaceae, are highly rearranged, causing the disruption of operons and loss of genes (Cosner et al, 1997;Cai et al, 2008;Haberle et al, 2008;Guisinger et al, 2011). It has been suggested that a higher number of repeat sequences present in these rearranged plastomes (Guisinger et al, , 2011 can promote illegitimate homologous recombination and cause these multiple structural changes (Maréchal and Brisson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Plastome organization, gene content, and gene order are generally well conserved among flowering plants. However, recent complete sequencing revealed that the plastomes in a few plant families, such as the Campanulaceae, Fabaceae, and Geraniaceae, are highly rearranged, causing the disruption of operons and loss of genes (Cosner et al, 1997;Cai et al, 2008;Haberle et al, 2008;Guisinger et al, 2011). It has been suggested that a higher number of repeat sequences present in these rearranged plastomes (Guisinger et al, , 2011 can promote illegitimate homologous recombination and cause these multiple structural changes (Maréchal and Brisson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although "indel" is shorthand for insertion/deletion, bona fide insertions are rare in angiosperm plastomes: The vast majority of evolutionary changes result from point mutations, tandem duplications, deletions, and small-scale rearrangements such as hairpin inversions or RNA-mediated intron loss (3,25,26). Previous reports of naturally occurring insertion of foreign (extraplastid) DNA were appropriately cautious because small segments of foreign DNA in intergenic regions may not be readily identified in comparisons among distantly related species (27,28). The newly sequenced plastomes provide unequivocal evidence of large, foreign DNA insertions that apparently contain protein-coding genes, which is unprecedented among angiosperms and account for many, but not all, of the genome rearrangements.…”
mentioning
confidence: 99%
“…However, this small size does not interfere with the G + C content, which is high. The plastid genomes of the closest Polytrichum species have a GC percentage of 28% to 33% [21,22] and those of seed plants range between 34% and 40% [50]. Cai et al, observed high G + C contents in the chloroplast coding regions, and certain regions had higher percentages than others, such as the IR region with its four genes with high levels of G and C [51].…”
Section: Discussionmentioning
confidence: 99%
“…Some genes seem to have been lost multiple times in the chloroplast and mitochondrial genomes during evolution [50], and other genes appear to be present or absent only in particular clades. For example, diverse genes are lacking in mosses and liverworts, such as rps16; however, the gene is present in hornworts and some vascular plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation